Association between serum 25-hydroxyvitamin D concentrations and platelet to high-density lipoprotein cholesterol ratio: evidence from two population-based studies - Wang, Ming; Huang, Zhi-Long; Rao, Cong-Liang; Zhu, Xing-Shu; Cheng, Bei-Jing; Zhu, Jun (Frontiers in Nutrition, 2025)
BackgroundThe platelet to high-density lipoprotein cholesterol ratio (PHR) is an emerging marker of inflammation and metabolic health, combining platelet counts and HDL cholesterol (HDL-C) levels. Vitamin D is essential for various physiologic processes, including immune modulation and lipid metabolism. Our study investigates the association between serum 25-hydroxyvitamin D [25(OH)D] concentrations and PHR.MethodsWe conducted cross-sectional analyses of two population-based datasets: NHANES (n = 36,238) from the U.S. and the baseline survey of a Chinese cohort study (n = 1,122). Serum 25(OH)D and blood PHR were assessed, with PHR defined as the ratio of platelet count to HDL-C (mmol/L). To examine the associations of 25(OH)D with PHR, we used weighted linear regression models and weighted restricted cubic splines (RCS), adjusting for potential confounders. Additionally, stratified analyses were performed based on potential influencing factors.ResultsAfter stepwise adjusting for cycles, demographic characteristics, lifestyle factors, and health conditions (including medication use), survey-weighted linear regression analysis of the NHANES database identified a significant negative association of serum 25(OH)D levels with PHR. Specifically, for every 1-unit increase in 25(OH)D, PHR decreased by 0.23 to 0.41 units across models. This association remained significant when comparing the highest quartile (Q4) to the lowest quartile (Q1) of 25(OH)D, with PHR decreasing by 14.84 to 27.65 units across models. RCS analysis further supported a linear negative association of 25(OH)D with PHR. Similar results were observed for 25-hydroxyvitamin D3 [25(OH)D3]. Furthermore, analyses in the Chinese population confirmed the inverse association between serum total 25(OH)D and PHR. Notably, the stronger association observed in females was consistent across both populations, with statistically significant interaction effects.ConclusionOur study found that serum 25(OH)D levels were significantly negatively correlated with PHR, particularly in females. These results suggest that 25(OH)D may help modulate PHR, with potential implications for disease prevention. Future research should confirm causality and explore underlying mechanisms.